Dhuha Prayer Habituation and Self-Regulation in Early Childhood: A Qualitative Study of Indonesian Kindergarten Children Aged 5–6 Years - Laela Lutfiana Rachmah; Alfarobi Ahmad Sulaiman; Mutiara Fahrunisa; Zainul Arifin; Azkiya Jihadi A'la (IJIP : Indonesian Journal of Islamic Psychology, 2026)
This study examines how the habituation of the dhuha prayer is experienced and interpreted in relation to observable self-regulatory behaviors in early childhood education. Adopting an interpretive phenomenological design, the research was conducted in one Islamic kindergarten where dhuha prayer forms part of the daily routine. Participants included children aged five to six years and educators directly involved in the ritual practice. Data were collected through non-participant observation, semi-structured interviews, and document analysis, and analyzed using interpretive thematic procedures with attention to variability and contextual constraints. Findings indicate that within the structured ritual context, patterns of behavioral order, situational emotional settling, attentional engagement, and emerging initiative were observable. Verbatim interview excerpts and field notes suggest that the predictable sequencing, collective participation, and guided structure of the activity coincided with the temporary alignment of regulatory behaviors. However, variability across children was evident, and behavioral patterns were context-bound rather than uniformly sustained across settings. The study does not claim causal effects or developmental trajectories. Instead, it documents how a culturally embedded religious routine functioned as a socially organized environment in which regulatory behaviors were more visibly structured. These findings contribute to interdisciplinary discussions by situating religious ritual within developmental psychology frameworks of environmental scaffolding and guided participation. Further multi-site, longitudinal, and multi-method research is needed to examine mechanisms, boundary conditions, and contextual influences more rigorously.